Practical Invalid Curve Attacks on TLS-ECDH - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Computer Security -- ESORICS 2015)

ECST – Extended Context-Free Straight-Line Tree Grammars - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas; Jeromin, Markus (Data Science - 30th British International Conference on Databases, BICOD 2015)

Understanding the Patient 2.0 - Geierhos, Michaela; Bäumer, Frederik S.; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context)

Understanding the Patient 2.0 - Geierhos, Michaela; Bäumer, Frederik S.; Schulze, Sabine; Klotz, Caterina (Modeling and Using Context)

Swarm in a Fly Bottle: Feedback-Based Analysis of Self-organizing Temporary Lock-ins - Hamann, Heiko; Valentini, Gabriele (Ninth Int. Conf. on Swarm Intelligence (ANTS 2014))

Generating EAST-ADL Event Chains from Scenario-Based Requirements Specifications - Koch, Thorsten; Holtmann, Jörg; DeAntoni, Julien (Software Architecture)
Real-time software-intensive embedded systems complexity, as in the automotive domain, requires rigorous Requirements Engineering (RE) approaches. Scenario-based RE formalisms like Modal Sequence Diagrams (MSDs) enable an intuitive specication and the simulative validation of functional requirements. However, the dependencies between events occurring in different MSD scenarios are implicit so that it is difficult to find causes of requirements defects, if any. The automotive architecture description language EAST-ADL addresses this problem by relying on event chains, which make dependencies between events explicit. However, EAST-ADL event chains have a low abstraction level, and their relationship to functional requirements has seldom been investigated. Based on the EAST-ADL functional architecture, we propose to use its central notion of event to conciliate both approaches. We conceived an automatic transformation from the high abstraction level requirements specified in MSDs to the low abstraction level event chains.

Use Your Best Device! Enabling Device Changes at Runtime - Bokermann, Dennis; Gerth, Christian; Engels, Gregor (12th International Conference on Business Process Management (BPM 2014))

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics, ALGOSENSORS 2013

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Aggregation of Network Protocol Data Near Its Source - Fourné, Marcel; Stegemann, Kevin; Petersen, Dominique; Pohlmann, Norbert (Information and Communication Technology)

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Separating Regular Languages by Piecewise Testable and Unambiguous Languages - Place, Thomas; van Rooijen, Lorijn; Zeitoun, Marc (Mathematical Foundations of Computer Science 2013 - 38th International Symposium, (MFCS) 2013, Klosterneuburg, Austria, August 26-30, 2013)

Fast Multi-update Operations on Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Jacobs, Thomas (Big Data - 29th British National Conference on Databases, BNCOD 2013,)

Evaluation of Rendering Algorithms Using Position-Dependent Scene Properties - Jähn, Claudius; Eikel, Benjamin; Fischer, Matthias; Petring, Ralf; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
In order to evaluate the efficiency of algorithms for real-time 3D rendering, different properties like rendering time, occluded triangles, or image quality, need to be investigated. Since these properties depend on the position of the camera, usually some camera path is chosen, along which the measurements are performed. As those measurements cover only a small part of the scene, this approach hardly allows drawing conclusions regarding the algorithm's properties at arbitrary positions in the scene. The presented method allows the systematic and position-independent evaluation of rendering algorithms. It uses an adaptive sampling approach to approximate the distribution of a property (like rendering time) for all positions in the scene. This approximation can be visualized to produce an intuitive impression of the algorithm's behavior or be statistically analyzed for objectively rating and comparing algorithms. We demonstrate our method by evaluating performance aspects of a known occlusion culling algorithm.

Real-Time 3D Rendering of Heterogeneous Scenes - Petring, Ralf; Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
Many virtual 3D scenes, especially those that are large, are not structured evenly. For such heterogeneous data, there is no single algorithm that is able to render every scene type at each position fast and with the same high image quality. For a small set of scenes, this situation can be improved if different rendering algorithms are manually assigned to particular parts of the scene by an experienced user. We introduce the Multi-Algorithm-Rendering method. It automatically deploys different rendering algorithms simultaneously for a broad range of scene types. The method divides the scene into subregions and measures the behavior of different algorithms for each region in a preprocessing step. During runtime, this data is utilized to compute an estimate for the quality and running time of the available rendering algorithms from the observer's point of view. By solving an optimizing problem, the image quality can be optimized by an assignment of algorithms to regions while keeping the frame rate almost constant.

Towards Swarm Calculus: Universal Properties of Swarm Performance and Collective Decisions - Hamann, Heiko; Engelbrecht, Andreas; Birattari, Mauro; Dorigo, Marco; Blum, Christian; Stuetzle, Thomas; Christensen, Anders Lyhne; Gross, Roderich (Swarm Intelligence: 8th International Conference, ANTS 2012)

Certifying RSA - Kakvi, Saqib; Kiltz, Eike; May, Alexander (Advances in Cryptology – ASIACRYPT 2012)

Optimal Security Proofs for Full Domain Hash, Revisited - Kakvi, Saqib; Kiltz, Eike (Advances in Cryptology – EUROCRYPT 2012)

Continuous Local Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Experimental Algorithms)

Local, Self-organizing Strategies for Robotic Formation Problems - Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Algorithms for Sensor Systems)

Newton’s Method and Secant Method for Set-Valued Mappings - Baier, Robert; Molo, Mirko Hessel-von (Large-Scale Scientific Computing)

Bleichenbacher’s Attack Strikes again: Breaking PKCS#1 v1.5 in XML Encryption - Jager, Tibor; Schinzel, Sebastian; Somorovsky, Juraj (Computer Security – ESORICS 2012)

Asynchronous Occlusion Culling on Heterogeneous PC Clusters for Distributed 3D Scenes - Suess, Tim; Koch, Clemens; Jähn, Claudius; Fischer, Matthias; Meyer auf der Heide, Friedhelm (Advances in Visual Computing)
We present a parallel rendering system for heterogeneous PC clusters to visualize massive models. One single, powerful visualization node is supported by a group of backend nodes with weak graphics performance. While the visualization node renders the visible objects, the backend nodes asynchronously perform visibility tests and supply the front end with visible scene objects. The visualization node stores only currently visible objects in its memory, while the scene is distributed among the backend nodes’ memory without redundancy. To efficiently compute the occlusion tests in spite of that each backend node stores only a fraction of the original geometry, we complete the scene by adding highly simplified versions of the objects stored on other nodes. We test our system with 15 backend nodes. It is able to render a ≈ 350,M polygons (≈ 8.5,GiB) large aircraft model with 20, to 30,fps and thus allows a walk-through in real-time.

Evolving for Creativity: Maximizing Complexity in a Self-organized Multi-particle System - Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (10th European Conference on Artificial Life (ECAL'09))

Modeling Agents and Agent Systems - Lettmann, Theodor; Baumann, Michael; Eberling, Markus; Kemmerich, Thomas (Transactions on Computational Collective Intelligence V)

Collisionless Gathering of Robots with an Extent - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; auf der Heide, Friedhelm Meyer; Raupach, Christoph; Swierkot, Kamil; et al. (SOFSEM 2011: Theory and Practice of Computer Science)

A New Approach for Analyzing Convergence Algorithms for Mobile Robots - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (Automata, Languages and Programming)

Exploiting New Interaction Techniques for Disaster Control Management Using Multitouch-, Tangible- and Pen-Based-Interaction - Nebe, Karsten; Klompmaker, Florian; Jung, Helge; Fischer, Holger Gerhard (Human-Computer Interaction. Interaction Techniques and Environments.)

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian (Human Centered Design)

Collisionless Gathering of Robots with an Extent - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (37th International Conference on Current Trends in Theory and Practice of Computer Science (SOFSEM 2011))
Gathering n mobile robots in one single point in the Euclidean plane is a widely studied problem from the area of robot formation problems. Classically, the robots are assumed to have no physical extent, and they are able to share a position with other robots. We drop these assumptions and investigate a similar problem for robots with (a spherical) extent: the goal is to gather the robots as close together as possible. More exactly, we want the robots to form a sphere with minimum radius around a predefined point. We propose an algorithm for this problem which synchronously moves the robots towards the center of the sphere unless they block each other. In this case, if possible, the robots spin around the center of the sphere. We analyze this algorithm experimentally in the plane. If R is the distance of the farthest robot to the center of the sphere, the simulations indicate a runtime which is linear in n and R. Additionally, we prove a theoretic upper bound for the runtime of O(nR) for a discrete version of the problem. Simulations also suggest a runtime of O(n + R) for the discrete version.

Energy-Efficient Strategies for Building Short Chains of Mobile Robots Locally - Brandes, Philipp; Degener, Bastian; Kempkes, Barbara; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Mixing Bottom-Up and Top-Down XPath Query Evaluation - Benter, Markus; Böttcher, Stefan; Hartel, Rita (East European Conference on Advances in Databases and Information Systems)

Updates on Grammar-Compressed XML Data - Bätz, Alexander; Böttcher, Stefan; Hartel, Rita (Advances in Databases - 28th British National Conference on Databases, BNCOD 28, Revised Selected Papers)

TraCX: Transformation of Compressed XML - Böttcher, Stefan; Hartel, Rita; Stey, Sebastian (Advances in Databases - 28th British National Conference on Databases, BNCOD 28, Revised Selected Papers)

A New Approach for Analyzing Convergence Algorithms for Mobile Robots - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (Automata, Languages and Programming)
Given a set of n mobile robots in the d-dimensional Euclidean space, the goal is to let them converge to a single not predefined point. The challenge is that the robots are limited in their capabilities. Robots can, upon activation, compute the positions of all other robots using an individual affine coordinate system. The robots are indistinguishable, oblivious and may have different affine coordinate systems. A very general discrete time model assumes that robots are activated in arbitrary order. Further, the computation of a new target point may happen much earlier than the movement, so that the movement is based on outdated information about other robot's positions. Time is measured as the number of rounds, where a round ends as soon as each robot has moved at least once. In [Cohen, Peleg: Convergence properties of gravitational algorithms in asynchronous robot systems], the Center of Gravity is considered as target function, convergence was proven, and the number of rounds needed for halving the diameter of the convex hull of the robot's positions was shown to be O(n^2) and Omega(n). We present an easy-to-check property of target functions that guarantee convergence and yields upper time bounds. This property intuitively says that when a robot computes a new target point, this point is significantly within the current axes aligned minimal box containing all robots. This property holds, e.g., for the above-mentioned target function, and improves the above O(n^2) to an asymptotically optimal O(n) upper bound. Our technique also yields a constant time bound for a target function that requires all robots having identical coordinate axes.

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Read-Write-Codes: An Erasure Resilient Encoding System for Flexible Reading and Writing in Storage Networks - Mense, Mario; Schindelhauer, Christian (Proceedings of 11th International Symposium on Stabilization, Safety, and Security of Distributed Systems)
We introduce the Read-Write-Coding-System (RWC) a very flexible class of linear block codes that generate efficient and flexible erasure codes for storage networks. In particular, given a message x of k symbols and a codeword y of n symbols, an RW code defines additional parameters k ≤ r,w ≤ n that offer enhanced possibilities to adjust the fault-tolerance capability of the code. More precisely, an RWC provides linear $\left(n,k,d\right)$-codes that have (a) minimum distance d=n-r+1 for any two codewords, and (b) for each codeword there exists a codeword for each other message with distance of at most w. Furthermore, depending on the values r,w and the code alphabet, different block codes such as parity codes (e.g. RAID 4/5) or Reed-Solomon (RS) codes (if r=k and thus, w=n) can be generated. In storage networks in which I/O accesses are very costly and redundancy is crucial, this flexibility has considerable advantages as r and w can optimally be adapted to read or write intensive applications; only w symbols must be updated if the message x changes completely, what is different from other codes which always need to rewrite y completely as x changes. In this paper, we first state a tight lower bound and basic conditions for all RW codes. Furthermore, we introduce special RW codes in which all mentioned parameters are adjustable even online, that is, those RW codes are adaptive to changing demands. At last, we point out some useful properties regarding safety and security of the stored data.

A Model of Symmetry Breaking in Collective Decision-Making - Hamann, Heiko; Meyer, Bernd; Schmickl, Thomas; Crailsheim, Karl (From Animals to Animats 11)

Robust Undetectable Interference Watermarks - Grza̧ślewicz, Ryszard; Kutyłowski, Jarosław; Kutyłowski, Mirosław; Pietkiewicz, Wojciech (ICCSA'05: Proceedings of the 2005 international conference on Computational Science and Its Applications)

Bregman Clustering for Separable Instances - Ackermann, Marcel R.; Blömer, Johannes (SWAT 2010)

Designing Self-healing in Automotive Systems - Seebach, Hella; Nafz, Florian; Holtmann, Jörg; Meyer, Jan; Tichy, Matthias; Reif, Wolfgang; Schäfer, Wilhelm (Lecture Notes in Computer Science)
Self-healing promises to improve the dependability of systems. In particular safety-critical systems like automotive systems are well suited application, since safe operation is required in these systems even in case of failures. Prerequisite for the improved dependability is the correct realization of the self-healing techniques. Consequently, self-healing activities should be rigorously specified and appropriately integrated with the rest of the system. In this paper, we present an approach for designing self-healing mechanisms in automotive systems. The approach contains a construction model which consist of a structural description as well as an extensive set of constraints. The constraints specify a correct system structure and are also used in the self-healing activities. We exemplify the self-healing approach using the adaptive cruise control system of modern cars.

Improved Hardness of Approximation for Stackelberg Shortest-Path Pricing - Briest, Patrick; Chalermsook, Parinya; Khanna, Sanjeev; Laekhanukit, Bundit; Nanongkai, Danupon (Workshop on Internet and Network Economics (WINE))

Preprocessed Global Visibility for Real-Time Rendering on Low-End Hardware - Eikel, Benjamin; Jähn, Claudius; Fischer, Matthias (Advances in Visual Computing)
We present an approach for real-time rendering of complex 3D scenes consisting of millions of polygons on limited graphics hardware. In a preprocessing step, powerful hardware is used to gain fine granular global visibility information of a scene using an adaptive sampling algorithm. Additively the visual influence of each object on the eventual rendered image is estimated. This influence is used to select the most important objects to display in our approximative culling algorithm. After the visibility data is compressed to meet the storage capabilities of small devices, we achieve an interactive walkthrough of the Power Plant scene on a standard netbook with an integrated graphics chipset.

Searchable Compression of Office Documents by XML Schema Subtraction - Böttcher, Stefan; Hartel, Rita; Messinger, Christian (Database and XML Technologies - 7th International XML Database Symposium, XSym 2010)

A Continuous, Local Strategy for Constructing a Short Chain of Mobile Robots - Degener, Bastian; Kempkes, Barbara; Kling, Peter; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Automata, Languages and Programming, 37th International Colloquium, ICALP 2010, Bordeaux, France, July 6-10, 2010, Proceedings, Part II.